SEJARAH BANJAR TRADISIONAL MENJADI LEMBAGA SOSIAL MASYARAKAT MODEREN DUSUN JURANG KOAK DESA BEBIDAS KECAMATAN WANASABA 2006-2015 - Hadi, Muhammad Shulhan; sawaluddin, Muhammad (Universitas Hamzanwadi, 2018)
Banjar in the Lombok is home to a collective spirit and ideas Sasak people, the spirit of mutual cooperation is very visible condensed running in the local wisdom ethnic Sasak. A close bond and sturdiness social life and sense of helping each other and need each other naturally born with and develop sponta. Banjar hambpir formed simultaneously with the formation of a shack in the villages in Lombok, when Law No. 5/1974 and Law No. 5/1979 on village administration was enacted, almost all the local knowledge coloring creativity diversity is turned off and terlibas by uniformity / uniformity village concept ala Jakarta, the banjo in Lombok seems lost and no longer function, now in an era of openness banjo as traditional roots ethnic sasak in Lombok is loaded with a spirit of togetherness / collective that emerged and developed back, the emergence banjar in Lombok is not like it used to be. The method used in solving the problem of this research is descriptive qualitative method, respondents, in this this study did not use population but use informants / study the methods used to collect the data are:Obsrvasi, interviews, Documentation. Based on the analysis in this study can be concluded that the revitalization of Banjar Traditional Being Society of Social Institutions of Modern Hamlet Canyons Koak Village Bebidas District of Wanasaba a creative efforts and systematic and continuing to strengthen the social capital that is in train, so that social energy was great and spontaneous in banjar be managed for productive things. Revitalization of traditional banjo is an answer to the question of socio- cultural people who have faced is poverty.